Physical education, gerontology and bioethics: perspectives on the autonomy of the elderly - Melo, Lucimauro Fernandes de; Goldim, José Roberto (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
This study is a literature review that seeks to demonstrate the views of Physical Education, Gerontology, and Bioethics regarding the Autonomy of the Elderly. The bibliographical research aimed to provide access to literature to analyze the studies already produced on the subject and was carried out with the studies related to the practices of the preparation of the Doctoral Thesis in Biomedical Gerontology at the Geriatrics and Gerontology Institute of the Pontifical Catholic University of Rio Grande do Sul. The theme is justified due to the importance it assumes in the current scientific scenario and in its discussions in a strategic dimension, which makes it important to emphasize and stimulate the practice of aging with health and quality. Autonomy, along with physical, mental, and psychological functions, is of utmost importance for a healthy aging process, promoting independence and dignity for the elderly to make their own choices. As a result of the research, it can be emphasized that it is essential to encourage the regular practice of aerobic physical activity or muscle strengthening, which bring changes for the adoption of an active lifestyle for the individual and is a fundamental part of an aging with quality and health. In this way, the study considers that Bioethics is concerned with the existing quality of life of human beings; since it follows with special attention the health areas; and observes the applicability and the relationship of its principles with the production of knowledge. The knowledge produced aims to understand the importance of Physical Education and also to verify if its practices are directed towards the studies of Gerontology and respect for the Autonomy of the Elderly.